Civilising rural Ireland The co-operative movement, development and the nation-state, 1889-1939 - Doyle, Patrick (Manchester University Press, 2019)
Civilising Rural Ireland examines how modern Ireland emerged out of the social and economic transformation prompted by the rural co-operative movement. The movement emerged in response to systemic economic problems that arose throughout the nineteenth century and coincided with a wide-ranging project of cultural nationalism. Within a short space of time the co-operative movement established a swathe of creameries, agricultural societies and credit societies, leading to a radical reorganisation of rural Ireland and helping to create a distinctive Irish political economy. The work of overlooked co-operative experts is critically examined for the first time and reinserted into the process of state development. The interventions of these organisers, intellectuals and farmers built up key institutions that shaped everyday life across rural communities. The movement weathered war and revolution, to become an indispensable part of an Irish state infrastructure after independence in 1922. The strained relationship and economic rivalry that developed between Irish and British co-operators is also explored in order to illuminate the changing relationship between Ireland and the United Kingdom from an economic perspective. Civilising Rural Ireland will appeal to a wide audience interested in modern Irish history and readers are introduced to an eclectic range of personalities who shared an interest in co-operation and whose actions possessed important consequences for the way Ireland developed. The creative use of local and national sources, many of which are examined for the first time, mean the book offers a new perspective on an important period in the making of modern Ireland.